Semiotics and the modern Quebec novel : a Greimassian analysis of Thériault's Agaguk - Perron, Paul (Toronto studies in semiotics., 1996)
The most popular novel in Quebec since the Second World War, Yves Theriault's Agaguk was published just before the Quiet Revolution, a period of major political and cultural transformation that radically altered Quebec society at the beginning of the 1960s. In this original socio-semiotic reading of the novel in translation, inspired by A.J. Greimas and the Paris School of Semiotics, Paul Perron examines the Inuit setting and characters of Agaguk as metaphors for Quebec society. Semiotics and the Modern Quebec Novel is one of the few semiotic analyses to deal with an entire novel, and illustrates the heuristic value of this complex methodology with respect to long prose texts in English.